Realism of Contemporary Society: A Mirror to Predominant Practices - Anand, Neha; Dhingra, Manish; Gola, Kamal Kumar; Rathore, Rahul (International Journal of Psychosocial Rehabilitation, 2020)
Beyond the shadow of the doubt it is well established fact that every society, regardless of the time, has its imperfections. Literature, being mirror to the society, depicts the realism of the society and paints the representation of the events in a matter of fact evading any kind of embellishment or glorification offering commentary of the contemporary society. Where many of the people are least concerned about the prevailing practices, some shoulder the responsibility of looking them straight in the eye and aspire to delineate them in a satirical way. . Chetan Bhagat, a well known author who holds the opinion that the young generation is on the verge of demolition, pens down about the youth, their ambitions and problems, their hardships, the tales of their success and failures, dowry system and generation gap. Youth of today are trapped in shackles of demons i.e. drinking, smoking, pre martial sex and illegal business. The present paper is an honest attempt to highlight realism of present-day society through the fictions of Chetan Bhagat.